2018
DOI: 10.1186/s12913-018-3495-x
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic differences in linkage error: an examination of four large-scale datasets

Abstract: BackgroundRecord linkage is an important tool for epidemiologists and health planners. Record linkage studies will generally contain some level of residual record linkage error, where individual records are either incorrectly marked as belonging to the same individual, or incorrectly marked as belonging to separate individuals. A key question is whether errors in linkage quality are distributed evenly throughout the population, or whether certain subgroups will exhibit higher rates of error. Previous investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 31 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…If there are linkage errors, analysts can determine methods or procedures to correct for this before conducting any analysis, while acknowledging this may not always be possible [ 7 ]. Analysts could identify linkage errors by analysing differences or similarities between linked and unlinked data [ 112 ], though this method may introduce additional bias caused by missing records [ 10 ]. A simulation exercise developed by Parrish, Shanahan [ 55 ] enables post-estimation of linkage errors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If there are linkage errors, analysts can determine methods or procedures to correct for this before conducting any analysis, while acknowledging this may not always be possible [ 7 ]. Analysts could identify linkage errors by analysing differences or similarities between linked and unlinked data [ 112 ], though this method may introduce additional bias caused by missing records [ 10 ]. A simulation exercise developed by Parrish, Shanahan [ 55 ] enables post-estimation of linkage errors.…”
Section: Discussionmentioning
confidence: 99%
“…The poor or lack of transparency in reporting data linkage processes, such as reports on linkage errors, may under or overestimate the quality of studies reported, particularly among the hard to reach populations as exemplified in these studies. The more vulnerable or hard to reach populations are often missed or miss matches, resulting in reduced sample size and loss of statistical power [ 10 , 129 ].…”
Section: Recommendations For Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…While data errors in real data are possible, the degree of corruption would be probably relatively low. According to the real NSWE and NCVRT datasets, the quality of data is very high with less than 1% linkage errors when a probabilistic two-database matching technique is applied on the unencoded NSWE dataset [52] and around 10% error in the NCVRT dataset. We have tested relatively pessimistic scenarios by synthetically including 20% and 40% corruption to the matching records in NCVR datasets.…”
Section: Discussionmentioning
confidence: 99%
“…They can be particularly useful for studying populations which are particularly hard to access with (that is, difficult to recruit into) traditional research studies. differs by socioeconomic characteristics, and was greater for younger individuals and those in rural areas (259). However, studies that take steps to minimise the effect of these limitations can provide useful, policy-relevant findings.…”
Section: Considerations For Research Using Linked Administrative Datamentioning
confidence: 99%